2014
DOI: 10.1676/13-084.1
|View full text |Cite
|
Sign up to set email alerts
|

Yolk mass variation in White-Rumped Swallows (Tachycineta leucorrhoa)

Abstract: Egg mass production is costly, but hatching from heavier eggs could be beneficial for the nestling's phenotype and fitness. Egg mass could be influenced by proximate causes, like food abundance, female condition, environmental conditions, and/or by ultimate causes, such as females depositing resources differentially within a clutch to increase the biological fitness of some eggs. Yolk mass, although poorly studied, is the source of nutrients for the embryo, so its mass should be more influential for the nestli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…In accordance with our expectation, the eggs laid under the poor food condition were significantly lighter in egg and yolk mass. The results are consistent with previous studies, suggesting that these egg characteristics are to a certain extent constrained by maternal nutrient and energy ingestion prior to or during egg-laying (Ruuskanen et al in press;Williams 1996;De Neve et al 2004;Ardia et al 2006;Karell et al 2008;Barrionuevo et al 2014). Food restriction did not Yolk mass (g) Figure 1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our expectation, the eggs laid under the poor food condition were significantly lighter in egg and yolk mass. The results are consistent with previous studies, suggesting that these egg characteristics are to a certain extent constrained by maternal nutrient and energy ingestion prior to or during egg-laying (Ruuskanen et al in press;Williams 1996;De Neve et al 2004;Ardia et al 2006;Karell et al 2008;Barrionuevo et al 2014). Food restriction did not Yolk mass (g) Figure 1.…”
Section: Discussionsupporting
confidence: 91%
“…; Barrionuevo et al. ). Food restriction did not disproportionally affect the yolk mass after controlling for egg mass, probably because during egg formation, yolk is formed before albumen and eggshell are wrapped up, and yolk mass is probably the determinant of albumen mass instead of the other way around (Williams ).…”
Section: Discussionmentioning
confidence: 96%
“…Like egg mass, yolk mass also increased with order of laying within clutches, as observed in previous studies of tree swallows (Ardia et al 2006), white-rumped swallows (Tachycineta leucorrhoa; Barrionuevo et al 2014), and red-winged blackbirds (Agelaius phoeniceus; Newbrey et al 2015), but in contrast to Chilean swallows (Tachycineta meyeni) for which size of yolk did not vary with laying order (Liljesthrom et al 2012). Since both egg mass and yolk mass increased with laying order in my study, it appears that nestlings hatching from later-laid eggs could benefit from both increased albumen proteins and increased yolk lipids.…”
Section: Egg and Yolk Masssupporting
confidence: 77%
“…Additionally, females that begin laying eggs earlier in the season are often older birds which lay heavier eggs than younger females, although yolk mass does not appear to differ between ages (Ardia et al 2006). Previous studies of tree swallows and other swallow species have found that both egg and yolk masses increase with increasing flying insect abundance (Ardia et al 2006;Whittingham et al 2007;Barrionuevo et al 2014), while yolk mass increases throughout the season and total egg mass is unrelated to when an egg is laid (Ardia et al 2006;Whittingham et al 2007;Liljesthrom et al 2012).…”
Section: Egg and Yolk Massmentioning
confidence: 99%
See 1 more Smart Citation